4 Ezra and 2 Baruch : translations, introductions, and notes - Stone, Michael E., 1938-; Henze, Matthias (Minneapolis. Fortress Press., 2013)
"Fresh translations of early Jewish texts 4 Ezra and 2 Baruch, written in the decades after the Judean War, which saw Jerusalem conquered, the temple destroyed, and Judaism changed forever. This handy volume makes these two important texts accessible to students, provides expert introductions, and illuminates the interrelationship of the texts through parallel columns" -- Publisher description.
"Study edition of two important ancient Jewish texts ... provides expert introductions, and illuminates the interrelationship of the texts through parallel columns"--Cover.
"Michael E. Stone has written the introductory remarks, the translation, and the commentary for 4 Ezra, and Matthias Henze has authored the corresponding sections for 2 Baruch"--page 2.
Includes bibliographical references (pages 17-18).
Keywords: Bible. -- Criticism, interpretation, etc; Syriac Apocalypse of Baruch -- Criticism, interpretation, etc; Criticism, interpretation, etc